2021
DOI: 10.2147/idr.s329708
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study of Malaria Trend in Libokemkem District Over the Last Five Years: North West Ethiopia

Abstract: Background: Malaria is a vector-borne disease caused by public health important Plasmodium species. Despite the fact that Ethiopia has implemented several malaria prevention and control techniques aimed at reducing its morbidity and death, it continues as major cause of morbidity and mortality in Ethiopia. Transmission dynamics are really critical for guiding the selection of the appropriate intervention in a given area. As a result, the goal of this study was to analyze the trend of malaria prevalence over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The mean TPR of this study is higher than that in the study conducted in Libokemkem District, Northwest Ethiopia. The difference might be that this study covers a large area, and the current study details the previous malaria status of the region [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mean TPR of this study is higher than that in the study conducted in Libokemkem District, Northwest Ethiopia. The difference might be that this study covers a large area, and the current study details the previous malaria status of the region [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…
Fig. 1 Map of study area: (a) Ethiopia, (b) Libo-Kemekem district, (c) Addis Zemen town, (d) Sheni river [ 22 ]
…”
Section: Methodsmentioning
confidence: 99%
“…Besides, there were 2 drugstores. In the town, there is the Sheni River, which is used for irrigation, swimming, washing clothes, and extracting sand for town residents [ 22 ]. Previous investigations have shown that the town of Addis Zemen has been considered a malaria spot area because large numbers of malaria cases have been recorded in the years [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, rapid diagnostic tests are performed, along with the adaptation of artemisinin-based drugs [5]. However, different transmission dynamics and trend analysis studies have elucidated that the number of cases is rising in Ethiopia [16][17][18][19]. The emergence and reintroduction of malaria in previously eliminated or reduced locations is becoming a new challenge for malaria elimination efforts [20].…”
Section: Introductionmentioning
confidence: 99%